Impaired renal conservation of sodium and chloride during sustained correction of systemic acidosis in patients with type 1, classic renal tubular acidosis. - Sebastian, A (1976)
In 10 patients with classic renal tubular acidosis in whom correction of acidosis was sustained with orally administered potassium bicarbonate, renal conservation of sodium was evaluated when dietary intake of sodium was restricted to 9--13 meq/day. In five patients, renal conservation of sodium was impaired by at least one criterion of impairment. In the remaining patients, renal conservation of sodium appeared to be relatively well-maintained, but an impairment could not be excluded. In each of six patients studied during induced water diuresis, including two in whom renal conservation of sodium was not unequivocally impaired, the minimal urinary concentrations of sodium were inappropriately high and the urinary excretion rates of sodium were flow-dependent. These results provide direct evidence that an abnormality in renal transport of sodium can occur in classic renal tubular acidosis, and compel a reconsideration of the pathophysiology of disordered renal transport of sodium in this disorder. The results indicate that in at least some patients with classic renal tubular acidosis impaired renal conservation of sodium is not exclusively a reversible consequence of the renal acidification defect. These findings raise the question whether renal transport of sodium is unimpaired in any patients with classic renal tubular acidosis. In the presently studied patients, the impairment in renal conservation of sodium appeared to be in part the consequence of an impaired ability of the vasopressin-responsive segments of the distal nephron to generate and maintain appropriately steep transepithelial sodium concentration gradients.